INFORMATION TECHNOLOGIES SPECIALISTS TRAINING IN HIGHER EDUCATION INSTITUTIONS OF UKRAINE: GENERAL STATE, PROBLEMS AND PERSPECTIVES - Proskura, С. Л.; Lytvynova, С. Г. (Journal of Information Technologies in Education (ITE), 2018)
The following article presents general state, problems and perspectives of specialists in information technologies training in higher education institutions of Ukraine, defines main problems of their training and outlines the prospects for improving informational and communicational competence of this area graduates. Ukrainian legislative base is studied on the point of programming students training, general directions of work connected to the development of mathematical, informational and software information systems in the field of information technologies are given. Also, the article contains a comparative diagram of tables with technologies and programming languages studied in the Ministry of Foreign Affairs of Ukraine, a survey of 2-year students of the Department of Automated Systems for Information Processing and Management of the Faculty of Computer Science and Elecrtonic Devices of the National Technical University of Ukraine "Kyiv Polytechnic Institute named after Igor Sikorsky" as well as market analysis of informational - communicational technologies of the IT market in Ukraine. We study web-oriented technologies of learning the basics of programming: compilers, automated programming verification systems, mind maps.